MORPHOLOGICAL VARIABILITY OF SEVERAL INDONESIAN POPULATIONS OF GIANT FRESHWATER PRAWN, Macrobrachium rosenbergii - Imron Imron; Iskandariah Iskandariah; Bambang Iswanto; Raden Roro Sri Puji Sinarni Dewi (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2008)
Patterns in morphological variability have been the main basis for conventional genetic improvement program, particularly in selective breeding. Proper understanding on these patterns hence, is of crucial prerequisite before any scheme of breeding program is undertaken. This study was aimed to explore those morphological variations with emphasis on the assessment of among-population and among-trait variations and assessment of predictive traits that may serve for inter-population differentiation. A total 281 individuals representing four natural populations (Asahan, Ogan, Barito, and Ciasem) and one domesticated stock (GIMacro) were sampled and analyzed for variability in thirteen morphological traits. While descriptive analyses were applied to analyze both among-stock and among-trait variations, discriminant function analysis was used to search for the best traits for interpopulation differentiation. The relative variability, expressed in the coefficient of variation (CV), was used to compare the amount and patterns of morphometric variability both among traits and between stocks. Results showed that total body weight was the most variable trait while the length and meristic traits were of lower level. Discriminant analysis found that rostrum length and abdoment length to be the best morphological discriminators among intraspecific populations. However, the continuous natures of these traits make them have limited applicability for intraspecific population differentiation.